Active Fire Dynamics in the Amazon: New Perspectives From High‐Resolution Satellite Observations. Issue 20 (16th October 2021) - Xu, Wenxuan; Liu, Yongxue; Veraverbeke, Sander; Wu, Wei; Dong, Yanzhu; Lu, Wanyun
Abstract: The Amazon region is expected to become an amplified fire‐prone system, but the mechanism of fire occurrence is not fully understood. Here, we employed more than 300, 000 Sentinel‐2 images acquired during 2016–2019 and compiled a high‐resolution inventory of active fires (AFs) over the Amazon. We found that the fire activities in the Amazon in 2019 did not stand out compared with those in 2017 as a whole. However, the number of fires increased in 2019 in the absence of an exceptional drought, suggesting increased human disturbance in the Amazon. The high‐resolution AF inventory further demonstrated that over 90% of detected AFs were associated with humans clearing deforested fields on forest fringes for agricultural land expansion. Additionally, our inventory indicated that satellite sensors with coarser spatial resolution could miss considerable small fires, especially at the sensitive agriculture–forest interface, which therefore should be targeted as a priority conservation area. Plain Language Summary: The Amazon region is a globally important biodiversity hotspot and carbon reservoir. In the context of increasing deforestation in the Amazon, high‐resolution satellite monitoring is essential for detecting small spatially fragmented fires and for developing more targeted forest conservation strategies. Here, we compiled a high‐resolution active fire inventory by processing more than 300, 000 Sentinel‐2 images. First, we found that most fires burn over shrublands, grasslands, and croplands near the fringes of the rainforest. Second, the headline‐grabbing fires in 2019 did not stand out compared with those in 2017 as a whole. However, the 2019 fires occurred in the absence of droughts, and more fires were observed deeper in the forest, suggesting that human disturbance was increasing in the Amazon. Finally, our inventory allows spatially explicit matches with fire‐affected land covers. Evidence from high‐resolution observations indicated that the fires in the Amazon are closely interlinked with deforestation and agricultural land expansion and form an interactive circle. This leads to forest fragmentation and stimulates more fragmented fires in turn. Our findings improve the understanding of fire–climate–land cover change interactions at a fine spatial resolution. Key Points: The fire dynamics in 2019 without an exceptional drought indicated an increase in human disturbance in the Amazon Over 90% of detected fires were associated with human clearing deforested fields on the forest fringes for agricultural purposes Small fires are well recorded in Sentinel‐2 images, providing a vital supplement to active fire products from coarser resolution sensors